Financial Sustainability of A Firm: Debt-based or Equity-based Financing to Pursue - Umul Ain’syah Sha’ari; Siti Raihana Bt Hamzah; Karmila Hanim Kamil (Bank Indonesia Institute, 2024)
Indexed by Scopus